Antifeedant Activity of Selected Botanicals Against the Larvae of Helicoverpa armigera (Hubner) - Arunagiri, V.; Sundararajan, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The cotton boll worm Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) is one of the most destructive pests of several crops such as cotton, corn, peanut, clover, vegetables and various fruits in India The sensitivity of Helicoverpa armigera 4th instar larvae towards the aqueous plant extracts (Artemisia vulgaris L. and Zanthoxylum asiaticum (L.) Appelhans, Groppo & J.Wen) were investigated under laboratory conditions and the effect of sublethal concentrations on the feeding deterrence were evaluated on the test organism. Results revealed that the 4th instar larvae of H. armigera was more susceptible to Artemisia extracts than Zanthoxylum extract as it has higher LC50 values. In addition, the results showed that the mean feeding deterrence (FDI%) of botanicals extracts was concentration-dependent. Therefore, these botanicals could be important as eco-friendly accessible pest control alternatives against H. armigera. The selected botanical extracts used in this study are among those compounds under investigation as potential natural pesticides.